2004
DOI: 10.1038/sj.leu.2403297
|View full text |Cite
|
Sign up to set email alerts
|

Direct cloning of leukemia-reactive T cells from patients treated with donor lymphocyte infusion shows a relative dominance of hematopoiesis-restricted minor histocompatibility antigen HA-1 and HA-2 specific T cells

Abstract: Donor T cells recognizing hematopoiesis-restricted minor histocompatibility antigens (mHags) HA-1 and HA-2 on malignant cells play a role in the antileukemia effect of donor lymphocyte infusion (DLI) in patients with relapsed leukemia after allogeneic stem cell transplantation. We quantified the contribution of HA-1 and HA-2 specific T cells to the total number of leukemia-reactive T cells in three HA-2 and/or HA-1 positive patients responding to DLI from their mHag negative donors. Clinical responses occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 50 publications
1
58
1
Order By: Relevance
“…It is still necessary to optimize culture conditions such as varying peptide length, adjusting the stimulation period for minimizing in vitro clonal contraction and incorporating positive selection before cloning to maximize the chance to identify multiple clones. 36 It would be interesting to know whether HLA-A*0201-restricted HA-1 H -specific CTLs raised by other researchers also fail to recognize the HA-1 H /A*0201 peptide, VLHDDLLEA, presented on HLA-A*0206 and whether our HLA-A*0206-restricted CTL clones that lysed HLA-A*0201 þ and HA-1 H LCL are relatively uncommon. To this end, it would be necessary to randomly raise CTL clones by single cell-sorting T cells strongly stained with either HLA-A*0206/HA-1 H or HLA-A*0201/HA-1 H tetramer.…”
Section: Discussionmentioning
confidence: 98%
“…It is still necessary to optimize culture conditions such as varying peptide length, adjusting the stimulation period for minimizing in vitro clonal contraction and incorporating positive selection before cloning to maximize the chance to identify multiple clones. 36 It would be interesting to know whether HLA-A*0201-restricted HA-1 H -specific CTLs raised by other researchers also fail to recognize the HA-1 H /A*0201 peptide, VLHDDLLEA, presented on HLA-A*0206 and whether our HLA-A*0206-restricted CTL clones that lysed HLA-A*0201 þ and HA-1 H LCL are relatively uncommon. To this end, it would be necessary to randomly raise CTL clones by single cell-sorting T cells strongly stained with either HLA-A*0206/HA-1 H or HLA-A*0201/HA-1 H tetramer.…”
Section: Discussionmentioning
confidence: 98%
“…18 Furthermore, we recently demonstrated that T cells contributing to the GVL reactivity of DLI can be isolated based on their production of IFNg. 36 Thus, Th1 cytokines play a very important role in antitumor reactivity. Th2 and Tc2 cells have also been suggested to play a central role in the regulation of GVHD, graft rejection, and GVL responses.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] However, CD4 þ T cells with direct cytolytic activity against leukemic cells have been isolated from patients with GvL responses, suggesting that CD4 þ T cells may also contribute to anti-tumor immunity as effector cells. 7,[12][13][14] This is also supported by clinical studies, which showed that depletion of CD8 þ T cells from the stem cell graft or DLI reduced the incidence and severity of GvHD without compromising GvL reactivity. 15,16 However, although these studies have demonstrated clinical efficacy of CD8-depleted DLI, it remains unclear whether clinical responses in these patients were directly mediated by CD4 þ T cells, or could be attributed to contaminating CD8 þ T cells in the DLI or residual donor-derived CD8 þ T cells in the patients.…”
Section: Introductionmentioning
confidence: 86%